Prestellar grain-surface origins of deuterated methanol in comet 67P/Churyumov–Gerasimenko. Issue 4 (31st October 2020) - Drozdovskaya, Maria N; Schroeder I, Isaac R H G; Rubin, Martin; Altwegg, Kathrin; van Dishoeck, Ewine F; Kulterer, Beatrice M; De Keyser, Johan; Fuselier, Stephen A; Combi, Michael
ABSTRACT: Deuterated methanol is one of the most robust windows astrochemists have on the individual chemical reactions forming deuterium-bearing molecules and the physicochemical history of the regions where they reside. The first-time detection of mono- and di-deuterated methanol in a cometary coma is presented for comet 67P/Churyumov–Gerasimenko using Rosetta –ROSINA data. D-methanol (CH3 OD and CH2 DOH combined) and D2 -methanol (CH2 DOD and CHD2 OH combined) have an abundance of 5.5 ± 0.46 and 0.00069 ± 0.00014 per cent relative to normal methanol. The data span a methanol deuteration fraction (D/H ratio) in the 0.71−6.6 per cent range, accounting for statistical corrections for the location of D in the molecule and including statistical error propagation in the ROSINA measurements. It is argued that cometary CH2 DOH forms from CO hydrogenation to CH3 OH and subsequent H–D substitution reactions in CH3 –R. CHD2 OH is likely produced from deuterated formaldehyde. Meanwhile, CH3 OD and CH2 DOD could form via H–D exchange reactions in OH–R in the presence of deuterated water ice. Methanol formation and deuteration is argued to occur at the same epoch as D2 O formation from HDO, with formation of mono-deuterated water, hydrogen sulphide, and ammonia occurring prior to that. The cometary D-methanol/methanol ratio is demonstrated to agree most closely with that in prestellar cores and low-mass protostellar regions. The results suggest that cometary methanol stems from the innate cold (10–20 K) prestellar core that birthed our Solar system. Cometary volatiles individually reflect the evolutionary phases of star formation from cloud to core to protostar.